Surface Modification via Dielectric Barrier Discharge Atmospheric Cold Plasma (DBD–ACP): Improved Functional Properties of Soy Protein Film - Zhibing Li; Shanggui Deng; Jing Chen (Foods, 2022)
Atmospheric cold plasma (ACP), a novel technology, has been widely adopted as an efficient approach in surface modification of the film. The effect of ACP treatment on the physicochemical and structural properties of soy protein film were investigated. As a result, the optimal conditions for the preparation of the film were determined for soy protein (10%), glycerol (2.8%), ACP treatment at 30 kV for 3 min, on the basis of elongation at the break, and water vapor permeability. Under the optimal conditions, the ACP–treated films exhibited enhanced polarity according to the increased values of solubility, swelling index, and moisture content, compared with the untreated counterpart. An increase in the hydrophilicity is also confirmed by the water contact angle analysis, which decreased from 87.9° to 77.2° after ACP pretreatment. Thermostability was also improved by ACP exposure in terms of DSC analysis. SEM images confirmed the tiny pores and cracks on the surface of film could be lessened by ACP pretreatment. Variations in the Fourier transform infrared spectroscopy indicated that some hydrophilic groups were formed by ACP pretreatment. Atomic force microscopy data revealed that the roughness of soy protein film which was pretreated by ACP was lower than that of the control group, with an Rmax value of 88.4 nm and 162.7 nm for the ACP- treated and untreated samples, respectively. The soy protein film was characterized structurally by FT–IR and DSC, and morphological characterization was done by SEM and AFM. The soy protein film modified by ACP was more stable than the control group. Hence, the great potential in improving the properties of the film enables ACP treatment to be a feasible and promising alternative to other modification methods.